Design and Optimization of Support and Drive System for Magnetic Levitation Air Compressor for Fuel Cells - Enhui Xing; Qi Gao; Yuanqi Dong; Wenxin Bai (Actuators)
The 5-degree-of-freedom active magnetic bearings (5-DOF AMB) and high-speed permanent magnet synchronous motor (HPMSM) were combined and applied to energy-recovery-type air compressors for fuel cells, which gives full play to the advantages of both and meets the design requirements for air compressors in fuel cells. Based on the energy recovery air compressor for fuel cells with a power of 30 kW and a rated speed of 100,000 rpm, this paper combined 5-DOF AMB with HPMSM and used it as its support and drive system. Multi-physics field and multi-objective optimization were carried out by integrating the multi-physics field with the Multi-objective Grey Wolf Algorithm (MOGWO), and the feasibility of the design of the system and its reliability were verified using finite element software.